How Is Global Commerce Affecting the Gender Composition of Employment? A Firm-Level Analysis of the Effects of Exposure to Gender Norms via Trade and FDI - Pia Heckl; Carolina Lennon; Alyssa Schneebaum (CESifo GmbH, 2025)
Global firms have a higher share of female employees than domestic non-exporters. To explain this fact, this paper tests whether international trade and FDI are channels through which norms regarding gender (in)equality are transmitted from customers and investors to firms. We employ pooled cross-sectional data from 2007 - 2016 for around 28,000 firms in 104 different countries. We compare global versus non-global firms in the same market to study the influence of firms' exposure to gender norms in commercial partner countries. The results show a race to the top for low- and mid-level jobs and the opposite for top managerial positions.
Keywords: F66; D22; F42; J16; 330; globalization; international trade; FDI; gender; transmission of social norms